1998
DOI: 10.1123/tsp.12.4.440
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Type of Sport and Time of Season on Athletes’ Use of Imagery

Abstract: Previous research (e.g., Barr & Hall, 1992) suggests that imagery is used differentially throughout an athlete’s competitive season. The influence of time of season (early vs. late) and type of sport (team vs. individual) on athletes’ use of imagery was examined. Male and female varsity athletes representing 10 sports completed the Sport Imagery Questionnaire (Hall, Mack, Paivio, & Hausenblas, in press) early and late in a competitive season. Results indicated that cognitive specific (CS) imagery signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 9 publications
6
43
1
3
Order By: Relevance
“…The current findings differ from the above as the data were collected no more than 24 hours prior to competition, thus athletes were probably not engaging in learning new skills and strategies. Munroe et al (1998) indicated that elite athletes may also use CS imagery to help them to remain focused on a forthcoming competition and to enhance the performance of well-learned skills and strategies. Therefore, it appears that elite athletes may use cognitive imagery during training as well as just prior to competition.…”
Section: Discussionmentioning
confidence: 98%
“…The current findings differ from the above as the data were collected no more than 24 hours prior to competition, thus athletes were probably not engaging in learning new skills and strategies. Munroe et al (1998) indicated that elite athletes may also use CS imagery to help them to remain focused on a forthcoming competition and to enhance the performance of well-learned skills and strategies. Therefore, it appears that elite athletes may use cognitive imagery during training as well as just prior to competition.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, no differences were found for sport type. Munroe et al (1998) found that type of sport influenced athletes' use of imagery, but they considered a wide variety of sports and did not categorize them into team and individual sports. The present findings suggest that when sports are simply classified as team and individual, no significant differences in the use of the five functions of imagery emerge in either competition or practice.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the Sport Imagery Questionnaire (Hall, Mack, Paivio, & Hausenblas, 1998) has led to the identification of five different functions of imagery: (a) cognitive specific (images of specific sport skills); (b) cognitive general (images of strategies, game plans or routines); (c) motivational specific (images related to an individual's goals); (d) motivational generalarousal (images associated with arousal, anxiety, and stress); and (e) motivational general-mastery (images of being mentally tough, in control, and selfconfident). Athletes report using all of these functions, but motivational general-mastery and cognitive specific imagery are typically employed the most frequently (Cumming & Hall, 2002b;Hall et al, 1998;Munroe, Hall, Simms, & Weinberg, 1998;Vadocz, Hall, & Moritz, 1997). Because the Sport Imagery Questionnaire measures the frequency of athletes' imagery in general and is not contextualized for a particular setting, it is unclear whether this pattern of use will differ for practice and competition.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research by Munroe, Hall, Simms, and Weinberg (1998) indicated that athletes use MG-M imagery to help themselves get through tough practices early in the season, whereas later in the season they use MS imagery to see themselves competing successfully. This raises important applied issues concerning the most effective time to use the different functions of imagery and in selecting teachable moments to introduce performers to the different functions.…”
mentioning
confidence: 98%